Induction of Labour at Term: Comparison of Prostaglandin E2 with Foley Catheter - Mehreen Yousaf Rana; Habiba Sharaf Ali; Ome Kulsoom; Rehana Yasmeen; Rabel Gul (ziauddin University, 2024)
Background: Induction of labour (IOL) or cervical ripening of an unfavourable cervix can be achieved by both pharmacological and surgical methods. When the cervix is unripe, Foley catheters and prostaglandins method of IOL is used. In this study, we aimed to compare the success rate and cost-effectiveness of vaginal prostaglandin E2 pessary with Foley catheter. Methods: This quasi-experimental study was conducted at the Gynaecological department of Ziauddin hospital from June-December 2019. A total of n=256 women at term were selected according to inclusion criteria. Group 1 was induced with Foley catheter and group 2 with Prostaglandins E2 vaginal pessary. The success rate to achieve delivery, the time interval between induction, delivery and the cost were recorded and compared between the two methods. Student's t-test (continuous variables) and Chi-square (categories) were used for statistical analysis and p-value < 0.05 was considered statistically significant. Results: The mean age of the females was 27.15 ± 5.5 years. The mean induction to the delivery time interval for PGE2 (group 2) was 15.77 ± 7.37 hours and Foley catheter (group 1) 17.31 ± 7.19 hours (p=0.02). The study did not find any statistically significant difference between the two methods of labour induction(p>0.05). It was found that overall, 198 (77.3%) women delivered by spontaneous vaginal deliveries and 58 (22.7%) by lower Caesarean section (p=0.02, 0.04). However, the total cost of prostaglandins (Rs.1500/-) was higher than the cost of Foley catheter (Rs. 256/-) (p=0.00). Conclusion: Foley catheter to induce labour in an unfavourable cervix is an effective, safe, and inexpensive method of labour induction. Keywords: Foley Catheter; Prostaglandin E2; Induction of Labour; Cost.